The Constitution as an Instrument for the Protection of Human Rights - Yunus, Nur Rohim (ADALAH, 2023)
The constitution is the highest fundamental law and is the main instrument in protecting human rights (HAM). This essay discusses the importance of the constitution in guaranteeing individual freedom and balancing state interests with citizen rights. However, implementing human rights in the constitution often faces a dilemma, especially when national interests clash with personal liberty. With a strong philosophical, sociological, and legal foundation, the constitution can effectively ensure justice and freedom for all. In addition, strengthening legal mechanisms, socialising human rights, harmonising with international standards, and increasing community participation are strategic steps to make the constitution the main pillar in enforcing human rights. Thus, the constitution is not only a legal text, but also a dynamic and adaptive tool for protecting rights to the development of the times.